Do Genetic Factors Modify the Relationship Between Obesity and Hypertriglyceridemia?: Findings From the GLACIER and the MDC Studies. (April 2016) - Ali, Ashfaq; Varga, Tibor V.; Stojkovic, Ivana A.; Schulz, Christina-Alexandra; Hallmans, Göran; Barroso, Inês; Poveda, Alaitz; Renström, Frida; Orho-Melander, Marju; Franks, Paul W.
Abstract : Background—: Obesity is a major risk factor for dyslipidemia, but this relationship is highly variable. Recently published data from 2 Danish cohorts suggest that genetic factors may underlie some of this variability. Methods and Results—: We tested whether established triglyceride-associated loci modify the relationship of body mass index (BMI) and triglyceride concentrations in 2 Swedish cohorts (the Gene–Lifestyle Interactions and Complex Traits Involved in Elevated Disease Risk [GLACIER Study; N=4312] and the Malmö Diet and Cancer Study [N=5352]). The genetic loci were amalgamated into a weighted genetic risk score (WGRSTG ) by summing the triglyceride-elevating alleles (weighted by their established marginal effects) for all loci. Both BMI and the WGRSTG were strongly associated with triglyceride concentrations in GLACIER, with each additional BMI unit (kg/m 2 ) associated with 2.8% ( P =8.4×10 –84 ) higher triglyceride concentration and each additional WGRSTG unit with 2% ( P =7.6×10 –48 ) higher triglyceride concentration. Each unit of the WGRSTG was associated with 1.5% higher triglyceride concentrations in normal weight and 2.4% higher concentrations in overweight/obese participants ( P interaction =0.056). Meta-analyses of results from the Swedish cohorts yielded a statistically significant WGRSTG ×BMI interaction effect ( P interaction =6.0×10 –4 ), which was strengthened by including data from the Danish cohorts ( P interaction =6.5×10 –7 ). In the meta-analysis of the Swedish cohorts, nominal evidence of a 3-way interaction (WGRSTG ×BMI×sex) was observed ( P interaction =0.03), where the WGRSTG ×BMI interaction was only statistically significant in females. Using protein–protein interaction network analyses, we identified molecular interactions and pathways elucidating the metabolic relationships between BMI and triglyceride-associated loci. Conclusions—: Our findings provide evidence that body fatness accentuates the effects of genetic susceptibility variants in hypertriglyceridemia, effects that are most evident in females. Abstract : Supplemental Digital Content is available in the text.